Homoeroticism in Imperial China : a sourcebook - Stevenson, Mark.; Wu, Cuncun. (Routledge, 2013)
"Bringing together over sixty pre-modern Chinese primary sources on same-sex desire in English translation, Homoeroticism in Imperial China is an important addition to the growing field of the comparative history of sexuality and provides a window onto the continuous cultural relevance of same-sex desire in Chinese history. Negotiating what can be a challenging area for both specialists and non-specialists alike, this sourcebook provides: - accurate translations of key original extracts from classical Chinese - concise explanations of the context and significance of each entry - translations which preserve the aesthetic quality of the original sources An authoritative and well organised guide and introduction to the original Chinese sources, this sourcebook covers histories and philosophers, poetry, drama (including two complete plays), fiction (including four complete short stories and full chapters from longer novels) and miscellanies. Each of these sections are organised chronologically, and as well as the general introduction, short introductions are provided for each genre and source. Revealing what is a remarkably sophisticated and complex literary tradition, Homoeroticism in Imperial China is an essential sourcebook for students and scholars of Imperial Chinese history and culture and sexuality studies"--